"Because Survival is Insufficient": Performing Virtual Shakespearean Tragedy in the Era of COVID-19 - Bruno, Ruby Rose (Trinity College Dublin. School of Creative Arts. Discipline of Drama, 2025)
During the height of the COVID-19 pandemic and its ensuing lockdowns in 2020-2021, many theatre-makers turned to online platforms such as Zoom and YouTube to produce online theatrical performances in the absence of in-person theatre opportunities. Two such projects, Sofa Shakespeare and The Show Must Go Online, both produced a series of Shakespearean plays that were created and performed fully online, with participants and audience members from around the globe. The history of Shakespearean performance during mass disease outbreaks dates back to the era in which the plays were written, and this thesis argues that online Shakespearean works produced during COVID-19 continued a well-established tradition of Shakespearean performance during mass disease outbreaks, but also used technological advancements to create new ways of working within the constraints of lockdown, effectively facilitated audience engagement and interaction, and fostered online community spaces that allowed participants to find connections with one another during a time of mass isolation and tragedy. This thesis uses three case studies (Sofa Shakespeare's Romeo and Juliet, The Show Must Go Online's Macbeth, and both projects' respective versions of Hamlet) to examine the ways in which these projects used Shakespeare as a means of facilitating online community during a time of mass tragedy and isolation, the ways in which the online platform could be used to enhance the central themes of the work, and the impact of the remaining "virtual ghosts" of these works in the online archival space. Much as Romeo and Juliet unites people who have been isolated from one another, or as ghosts appear in Hamlet to connect the characters to the past, this thesis will demonstrate how Shakespearean performance during COVID-19 inspired connection and innovation across distances while also maintaining a link between pandemics past and present.
APPROVED
Keywords: Shakespeare; tragedy; COVID-19; pandemic; plague; disease; Zoom; theatre; virtual theatre; digital theatre; The Show Must Go Online; Sofa Shakespeare; Hamlet; Macbeth; Romeo and Juliet; death; technology; lockdown; quarantine; YouTube; audience engagement; online community; social media